2020
DOI: 10.1101/2020.04.20.047134
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Harmful DNA:RNA hybrids are formedin cisand in a Rad51-independent manner

Abstract: DNA:RNA hybrids constitute a well-known source of recombinogenic DNA damage. The current literature is in agreement with DNA:RNA hybrids being produced co-transcriptionally by the invasion of the nascent RNA molecule produced in cis with its DNA template. However, it has also been suggested that recombinogenic DNA:RNA hybrids could be facilitated by the invasion of RNA molecules produced in trans in a Rad51-mediated reaction. Here, we tested the possibility that such DNA:RNA hybrids produced in trans constitut… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The mechanism of R-loop formation by APOLO has remained unknown. In S. cerevisiae, it has been reported that Rad51p mediates hybridization of transcripts to homologous chromosomal loci distinct from their site of synthesis [78], though another paper disputed this conclusion [79]. Finally, R-loop formation is well documented for the bacterial CRISPR-Cas9 DNA endonuclease [80], in which Cas9 bends the DNA to allow guide RNA infiltration into the double helix.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of R-loop formation by APOLO has remained unknown. In S. cerevisiae, it has been reported that Rad51p mediates hybridization of transcripts to homologous chromosomal loci distinct from their site of synthesis [78], though another paper disputed this conclusion [79]. Finally, R-loop formation is well documented for the bacterial CRISPR-Cas9 DNA endonuclease [80], in which Cas9 bends the DNA to allow guide RNA infiltration into the double helix.…”
Section: Discussionmentioning
confidence: 99%
“…DNA: RNA hybrids constitute a well-known source of recombinogenic DNA damage [71]. Spontaneous mitotic recombination is a well-known process, and it is also enhanced by transcription [72].…”
Section: Sars-cov-2 Vaccine Developmentmentioning
confidence: 99%
“…Also, there are several evidences for live, attenuated viral RNA vaccines to recombine with similar or other viral genome in circulation in the recipient's plasma, affecting the effectiveness of RNA vaccines [69,70]. DNA: RNA hybrids constitute a well-known source of recombinogenic DNA damage [71].…”
Section: Sars-cov-2 Vaccine Developmentmentioning
confidence: 99%